Application of the Make A Match Learning Model to Develop Student’s Social Skills in Elementary School Grade IV Interview Materials - Maulidah Rizkiyah; Aninditya Sri Nugraheni (South Sulawesi Education Development (SSED), 2025)
This study aims to analyze the application of the Make A Match learning model in developing students’ social skills in interview materials in grade IV elementary school. The research uses a descriptive qualitative approach with data collection through interviews and documentation involving classroom teachers and students’ social skills, especially cooperation and communication. Card matching activities encourage interaction, critical thinking, and create a fun learning atmosphere. Obstacles such as difficulty conditioning students after physical activity and preparation of complex materials can be overcome with engaging learning strategies and active teacher involvement. This model has the potential to be an effective solution to improve the quality of Indonesian learning and develop social skills of elementary school students.